A NOTE ON FRAME SYNCHRONIZATION SEQUENCES - Thokozani Shongwe; Victor N. Papilaya (Fakultas Teknik Elektronika dan Komputer Universitas Kristen Satya Wacana, 2012)
An introduction into binary sequences used for frame synchronization is given, together with criteria used in designing and/or finding optimal sequences that can be used as markers. Two approaches to the choice of optimal sequences for frame synchronization are presented, one approach focuses on the good properties of the marker and the other focuses on both marker and the data used in a frame. To illustrate the importance of “good” marker choice, simulations are presented showing the performance of “good” and “bad” marker choices.